InVO4–BiVO4 composite films with enhanced visible light performance for photodegradation of methylene blue - Lamdab U. (2017)
© 2016 Elsevier B.V. The InVO 4 , BiVO 4 , and InVO 4 –BiVO 4 films were fabricated by a simple doctor blading coating technique. The film thickness of the as-prepared samples was varied to one, two and three layers. The prepared InVO 4 –BiVO 4 composite films were characterized in detail by various analytical techniques that reveal the well crystallinity with orthorhombic structure of InVO 4 and monoclinic structure of BiVO 4 for the as-prepared material. The as-synthesized photocatalyst films were used as the efficient photocatalysts for the photocatalytic degradation of methylene blue (MB) under visible light illumination. It was found that the three-layered 0.2InVO 4 –0.8BiVO 4 film presented better photocatalytic activity than that of pure phase InVO 4 and BiVO 4 . About 70% of the 1 × 10 −5  g L −1 MB was degraded within 120 min catalyzed by the three-layered 0.2InVO 4 –0.8BiVO 4 films. Interestingly, an obvious synergy between two catalysts was observed and corresponding mechanism based on facilitated transfer of electrons and holes as a result of a suitable energy level alignment was suggested. Fluorescence method with terephthalic acid (TA) as the probe was employed for the quantification of hydroxyl production.